EFEKTIFITAS PELAYANAN APARATUR SIPIL PADA BIDANG PELAYARAN DINAS PERHUBUNGAN PROVINSI JAWA BARAT - Fitra Nurhakim; Sri Lestari (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
The concept of work effectiveness is basically designed to assess the work results achieved in accordance with a predetermined plan, at the discretion of the individual, or in other terms, to realize certain goals; thus, when these conditions are met, it is categorized as effective. This study describes the effectiveness of civil service in the Shipping Sector of the West Java Provincial Transportation Service. The methodological framework used in this study requires a comprehensive examination of the existing literature (library research). The data collection process is carried out through a comprehensive library study. Such library studies involve the aggregation of pre-existing data, followed by a critical analysis of the conclusions drawn from each source, which are then used as literature and reference materials for the purpose of understanding and analyzing the study. The findings of the current empirical investigation indicate that there are 3 aspects seen in the effectiveness of civil service in improving public services, namely the time factor, the accuracy factor and the service delivery style factor.